Ranking of sailing routes according to the potential number of groundings - Lušič, Zvonimir; Kos, Serdjo (Transport, 2013)
The paper presents the selection of ship sailing routes in the coastal area according to the probability of grounding. Taking into consideration the dangers in the heading direction as well as the vicinity and length of the coastline parallel to the ship course, the paper will try to propose a model for choosing the sailing route with the smallest possibility of grounding. The estimation of the dangers on the routes will be based on the potential number of groundings; human factor will not be taken into account, assuming that a human error on each route will have the same probability of occurrence. First Published Online: 11 Oct 2013